Durability of textile facing materials for construction: Operating accelerated ageing protocol results in basic medium for lifetime estimation in conditions of use. (September 2016) - Krimi, Imane; Ducoulombier, Laure; Dakhli, Zakaria; Lafhaj, Zoubeir
The building industry is now evolving in a rapid pace due to the massive need to build and rebuild the cities. While designing the building, the owner appreciates the esthetic aspects, whereas the contractor is more interested in a performance-based approach for its construction. The current study investigates the integration of industrial textiles in buildings. For that, life spawn estimation of textile materials is crucial due to the different existing French regulations that set a minimum durability criterion. The paper presents a methodology for lifetime estimation and an application to two fabrics intended for use as facing materials for buildings. A series of aging tests were carried out and extrapolations were made to reach the research goal. The results of tests that were carried out indicate the feasibility of the textiles' lifetime estimation methodology used.